2018
DOI: 10.1016/j.ajps.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Predicting oral disintegrating tablet formulations by neural network techniques

Abstract: Oral Disintegrating Tablets (ODTs) is a novel dosage form that can be dissolved on the tongue within 3min or less especially for geriatric and pediatric patients. Current ODT formulation studies usually rely on the personal experience of pharmaceutical experts and trial-and-error in the laboratory, which is inefficient and time-consuming. The aim of current research was to establish the prediction model of ODT formulations with direct compression process by Artificial Neural Network (ANN) and Deep Neural Netwo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 22 publications
(27 reference statements)
2
60
0
Order By: Relevance
“…Currently, only two deep learning approaches have been reported for formulation prediction 25. , 44.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, only two deep learning approaches have been reported for formulation prediction 25. , 44.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this research still needs significant improvement on methodology for formulation prediction. Recently deep learning with MD-FIS was applied for formulation prediction of oral fast disintegrating tablets 25 . The results showed that the prediction of deep learning was better than that of ANN because deep learning could extract the features automatically without designing feature extractors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Run et al established a prediction model for the disintegration time of oral disintegrating tablets, and the model achieved 80% accuracy. 15 Recently, applications of artificial intelligence engines, derived from the random forest algorithm, were demonstrated toward the analysis of internal tablet defects. 1 In this study, quantitative analyses of internal tablet crack severity were achieved based on the machine learning program.…”
Section: Introductionmentioning
confidence: 99%
“…49,50 In recent years, many successes have also been made by deep learning in drug discovery and formulation development. 51,52 For examples, in the year 2013, compared with other machine learning methods, deep learning yielded good performance in aqueous solubility prediction based on the undirected graphs. 53 In the year 2015, it was found that deep learning could reach or exceed the performance of the RF algorithms on a series of Merck's drug discovery datasets.…”
Section: Introductionmentioning
confidence: 99%